PENGARUH KINERJA LINGKUNGAN, PENGUNGKAPAN AKUNTANSI LINGKUNGAN, DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DAN KINERJA PASAR (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024) - Merinda Citra Saphira; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2025)
This research aims to provide empirical evidence regarding the influence of environmental performance, environmental accounting disclosure, and good corporate governance mechanism on financial performance and market performance, grounded in legitimacy theory and type II agency theory. Using a quantitative approach with multiple linear regression, this research analyzes 88 observations from 22 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021-2024. Variable measurements were conducted using several indicators, including the PROPER score of environmental performance, the GRI index for environmental disclosure, as well as board of commissioners’ activities, audit committee activities, and audit quality as proxies for GCG mechanism. Data were sourced from financial statements, annual reports, and sustainability reports, then analyzed using software SPSS software.Results show that environmental performance has a positive effect on financial performance and market performance, and board of commissioners’ activities also have a positive effect on financial performance. Conversely, audit committee activities have a negative effect on financial performance. Audit quality has a positive effect on market performance but does not affect financial performance. Meanwhile, environmental accounting disclosure does not affect either type of performance, and board of commissioners and audit committee activities also does not affect market performance.